2016
DOI: 10.1007/s00109-016-1409-0
|View full text |Cite
|
Sign up to set email alerts
|

CLEC5A is critical for dengue virus-induced osteoclast activation and bone homeostasis

Abstract: Osteoclasts are bone tissue macrophages critical to maintain bone homeostasis. However, whether osteoclasts are susceptible to flaviviral infections and involved in dengue virus (DV)-induced disease pathogenesis is still unknown. In this study, we found that osteoclasts were preferentially susceptible to DV infection and produced similar amounts of cytokines and infectious virions as macrophages. Interestingly, DV-induced cytokine secretion and nuclear translocation of the transcription factor NFATc1 in osteoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 33 publications
1
21
1
Order By: Relevance
“…Osteoclasts are multinucleated giant cells that differentiate from macrophages and are involved in bone remodeling [116]. DV infection of osteoclasts was recently shown to upregulate osteolytic activity [117]. Attenuation of DV-induced osteolytic activity was observed in MDL-1 -/- mice and, consistently, administration of a MDL-1 antagonist in wild-type mice also inhibited DV-activated osteolytic activity [117].…”
Section: Myeloid C-type Lectins Receptors—pattern Recognition Recementioning
confidence: 99%
“…Osteoclasts are multinucleated giant cells that differentiate from macrophages and are involved in bone remodeling [116]. DV infection of osteoclasts was recently shown to upregulate osteolytic activity [117]. Attenuation of DV-induced osteolytic activity was observed in MDL-1 -/- mice and, consistently, administration of a MDL-1 antagonist in wild-type mice also inhibited DV-activated osteolytic activity [117].…”
Section: Myeloid C-type Lectins Receptors—pattern Recognition Recementioning
confidence: 99%
“…Moreover, dengue virus activates the NLRP3 inflammasome via CLEC5A to induce the production of IL-1β and IL-18 6 , 7 . We have previously shown that dengue virus activates CLEC5A to upregulate osteolytic activity and dysregulate bone homeostasis 8 . Blockade of CLEC5A by anti-CLEC5A monoclonal antibody (mAb) not only attenuates dengue virus-induced and Japanese encephalitis virus-induced lethality, but also suppresses dengue virus-mediated activation of the NLRP3 inflammasome and osteolytic activity 4 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that dengue virus activates CLEC5A to upregulate osteolytic activity and dysregulate bone homeostasis 8 . Blockade of CLEC5A by anti-CLEC5A monoclonal antibody (mAb) not only attenuates dengue virus-induced and Japanese encephalitis virus-induced lethality, but also suppresses dengue virus-mediated activation of the NLRP3 inflammasome and osteolytic activity 4 , 8 . These findings suggest that CLEC5A has critical functions in flavivirus-induced inflammatory reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Members of C-type lectins have been shown to be crucial pattern recognition receptors that recognize members of the flavivirus and influenza virus families. Spleen tyrosine kinase (Syk)–coupled C-type lectin member 5A (CLEC5A) is the pattern recognition receptor (PRR) for the dengue virus (DV) 14 16 , Japanese encephalitis virus (JEV) 17 , and influenza virus H5N1 18 . These viruses can activate CLEC5A to secrete abundant proinflammatory cytokines from macrophages and myeloid cells; blockade of CLEC5A can protect mice from DV- and JEV-induced lethality and neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%